Synthesis and photoluminescence modulating of polypyrrole fluorescent nano-spheres/dots. Issue 28 (1st March 2016) - Dong, Ben; Yang, Mei; Ge, Shusheng; Cao, Yi; Li, Baoyan; Lu, Yun
Abstract : Polypyrrole fluorescent nanospheres/dots with tunable band gaps have been successfully synthesized, which showed the outstanding characteristics of low cytotoxicity, good biocompatibility and high luminescence stability. Abstract : Polypyrrole (PPy) nanospheres with an average diameter of 20 nm were successfully synthesized by simply using 3-chloroperbenzoic acid in pure ethanol. As-prepared PPy nanospheres showed a moderate photoluminescence signal with a quantum yield (QY) of 2.2% and excitation-dependent photoluminescence characteristics. To carry out the PPy nanosphere surface functionalization, PEG2000, 4, 7, 10-trioxa-1, 13-tridecanediamine and ethylenediamine severed respectively as surface passivating agents, and accordingly 5.5 nm, 4.5 nm and 3 nm sized nanodots were obtained, which exhibited enhanced fluorescence intensity with maximum QYs of 3.1%, 13% and 40% respectively and tunable band gaps in the range of 0.78–1.53 eV. These results were attributed to the increased electron density in PPy fluorescent nanospheres/dots. These resultant PPy fluorescent nanodots could be appropriately applied as cell-imaging agents, fluorescent inks and pH sensors owing to their outstanding characteristics of low cytotoxicity, good biocompatibility and high luminescence stability.